Ambient salinity affects silver nanoparticles (AgNPs) induced toxicity in the marine bivalve, the rock oyster, Saccostrea cucullata - Saeed Sadri; Arash Javanshir Khoei (Aquaculture Reports, 2023)
Silver nanoparticles (AgNPs) penetrate water sources in a variety of ways. Although some studies have reported their toxicity experimentally, little is known on the interactive impacts of nanoparticles and environmental factors on sea organisms. We investigated the interactions of salinity changes and AgNPs exposure in the rock oyster, Saccostrea cucullata off the Oman sea. The exposure test was done by challenging the oysters with environmentally relevant concentrations of AgNPs (Low concentration: 10 µg/l, middle concentration: 20 µg/l, high concentration: 30 µg/l) at different salinities (Low salinity: 12 g/l, middle salinity: 24 g/l, high concentration: 36 g/l) for 30 days, and then the immune components in hemolymph [Total hemocyte concentration (THC), phagocytosis], antioxidant enzyme activities [superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione S-transferase (GST)] in digestive gland, oxidative stress index (MDA: malondialdehyde) and immune-related gene expressions (pro-Cathepsin L, Rho protein, Ficolin, LPS/−1,3-glucan protein, DOCK 180 protein, Lysozyme, Defensin) in hemocyte were measured. Exposure of oysters to 20–30 µg/l AgNPs at 24 and 36 g/l salinities significantly increased hemocyte counts, phagocytosis, antioxidant enzyme activities and also up-regulated immune-related gene the expressions compared to 10 µg/l AgNPs treatment (P < 0.05). At salinity, 12 g/l, the exposure of the oysters to 10–30 µg/l AgNPs significantly decreased hemocyte counts, phagocytosis, antioxidant enzymes, and down-regulated the immune-related gene expressions (P < 0.05). In same salinity, GST activity showed significant decreases in the oysters exposed to 20–30 µg/l AgNPs (P < 0.05). The oxidative stress index (MDA) significantly elevated at salinity of 12 g/l (for oysters exposed to 10–30 µg/l AgNPs) and 24–36 g/l (for oysters exposed to 20–30 µg/l AgNPs). The results of the present study showed that a decrease in water salinity with can intensify toxicity in the rock oyster.